Improving magnetic cooling efficiency and pulldown by varying flow profiles. (October 2022) - Masche, M.; Liang, J.; Engelbrecht, K.; Bahl, C.R.H.
Highlights: Electrically actuated solenoid valves adjusted blow fractions between 25 and 47%. Increasing the blow fraction enhanced the device's cooling capacity and efficiency. Low blow fractions can reduce temperature pulldown time by 60%. A blow fraction of 41.7 % resulted in a maximum second-law efficiency of 27.3%. Performance losses of 49% or more when the cold and hot blows are not similar. Abstract: Magnetic refrigeration systems are promising cooling solutions that employ the active magnetic regenerator refrigeration cycle to achieve practical temperature spans and environmental benefits. The hydraulic system that ensures a continuous flow of the heat transfer fluid through the system with a reciprocating flow in each regenerator bed is critical to the performance of the refrigeration cycle. Hence, we investigate the characteristics of the parallel flow circuit of a rotary active magnetic regenerator system, which consists of thirteen trapezoid-shaped regenerators, each filled with 295 g of gadolinium spheres. Fluid flow is controlled via electrically actuated solenoid valves (both piloted and direct-acting) connected to the regenerator hot side. By varying the percentage of opening of the control valves, different blow fractions (or fluid flow waveforms) could be investigated. The objective of the study is twofold: (i) assess whether flow imbalances of the heat transfer fluid exist in the cold-to-hot blow (cold blow) and hot-to-cold blow (hot blow) directions, and (ii) determine whether there is an optimal value of the blow fraction both to maximize the cooling performance and realize a rapid temperature pulldown. Flow resistance measurements demonstrate a symmetric flow circuit design and resistances that are similar in the cold and hot blow directions. Moreover, for the studied temperature spans of 6 K and 16 K, the best blow fraction was found to be about 41.6 %. For instance, at a 16 K span, a utilization of 0.32, and at 1.4 Hz, increasing the fluid blow fraction from 25.0 to 41.6 % enhanced the cooling capacity and second-law efficiency from 70 to 330 W and from 2.6 to 17.4 %, respectively. In turn, lower blow fractions favored a more rapid temperature pulldown. The magnetocaloric system was about 30 % faster in establishing approximately 14 K temperature span when the blow fraction was reduced from 41.6 to 30.6 %. Hence, magnetic refrigeration systems can benefit greatly from solenoid valves, which allow the system to operate either in a time-saving mode or an energy-saving mode.